Migration and integration : an integrative review of relevant theories - Alshaer, Amjad (2024)
In this thesis, I address the phenomenon of migration and integration to explore the theoretical frameworks and evidence that shape our understanding of these processes. I review migration, its definitions, and types, in addition to the main theories related to it, such as push and pull factors, social network theory, and dual labor market theory, providing a basic understanding of the reasons and factors for the migration of individuals and societies. I also address the concept of integration and other terms, such as assimilation, adaptation, and acculturation, to highlight the multifaceted nature of cultural and social adaptation in the societies people migrate to. I also discuss theories that explain integration, focusing on social and human capital theories, and explain how they can be frameworks to understand migration theories and help provide a comprehensive analysis of the integration process. Based on a literature review methodology, this research brings together insights from various studies and articles written by experts in the field. It provides evidence-based recommendations to enhance migrant integration and foster more inclusive societies.